A Case Study Identified a New Mutation in the TTN Gene for Inherited Hypertrophic Cardiomyopathy - Dong J; Liu M; Chen Q; Zha L (International Journal of General Medicine)
Jiangtao Dong,1– 4,* Meilin Liu,1– 3,* Qianwen Chen,1– 3,5 Lingfeng Zha1– 3 1Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Key Laboratory of Biological Targeted Therapy, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 3Hubei Provincial Engineering Research Center of Immunological Diagnosis and Therapy for Cardiovascular Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 4Department of Cardiovascular Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 5Department of Pediatric Cardiology, Maternal and Child Health Hospital of Hubei Province, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingfeng Zha, Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jiefang Avenue, Wuhan, 430022, People’s Republic of China, Tel +86-15827177185, Email zhalf@hust.edu.cnBackground: Hypertrophic cardiomyopathy (HCM) is the most common hereditary cardiomyopathy, with variable pathogenesis, clinical presentation, and prognosis. Although mutations in genes encoding sarcomere proteins have been reported to explain the genetic etiology of 40%-60% of HCM patients, the etiology of approximately 1/3 of HCM patients remains unknown. Whole-exome sequencing (WES) is an effective method for identifying the genes that cause genetic diseases. In the present study, WES and systematic genetic screening were performed to determine the genetic causes of HCM in Chinese HCM family.Materials and Methods: Peripheral blood genomic DNA was collected from 9 family members of a Chinese Han HCM pedigree, including an HCM proband. Candidate variants obtained by WES were verified using Sanger sequencing, pathogenic mutation screening was conducted among family members, and the mutations were systematically analyzed using bioinformatics.Results: WES revealed a novel heterozygous missense mutation, c.20233 C>T (p.R6745C), located in exon 80 of the HCM-related gene TTN, which may be a pathogenic mutation in the family. In addition, this mutation was predicted to damage protein function. WES combined with Sanger sequencing results showed that the other two HCM patients in this family carried this TTN mutation, while none of the healthy family members carried the mutation except for a 3 years old girl.Conclusion: In this study, a new pathogenic mutation of TTN was found in a Chinese family with HCM, and disease-causing gene carriers in the family members were identified through pedigree screening. These findings have theoretical and application value for understanding the genetic basis of HCM, as well as for early risk stratification and early prevention and intervention of patients, and highlight the important role of genetic testing in the diagnosis and treatment of genetic diseases.Keywords: cardiomyopathy, HCM, whole exome sequencing, TTN, genetic testing